Pendampingan Rekonstruksi Harga Pokok Produksi dan Pemetaan Strategi Bisnis pada UMKM Salad Janah - Sulhani Sulhani; Yasminnasywa Iskandar; Jilan Sajida (Tazkia Islamic University College, 2026)
This study aims to accurately calculate the cost of production (HPP) using the full-costing method for Salad Jannah, an MSME in the culinary sector in Pekanbaru. Salad Jannah faces challenges such as fluctuating raw material prices and the high perishability of fresh fruit products. The research method used is a descriptive quantitative approach through interviews and documentation. The results show that the cost of production per unit for fruit salad is Rp14,844 and for jelly salad is Rp11,604. With the current selling price, the gross profit margin for fruit salad is 49% and for jelly salad is 42%. The study recommends cost management strategies through just-in-time procurement and marketing strategies such as product bundling and size diversification to increase revenue and maintain business sustainability.